2017
DOI: 10.1111/jvim.14816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic‐assisted Gastropexy on Gastrointestinal Transit Time in Dogs

Abstract: BackgroundProphylactic gastropexy has been promoted as a means of preventing gastric volvulus during gastric dilatation and volvulus (GDV) syndrome. Little is known about the impact of gastropexy on gastrointestinal transit time.HypothesisLaparoscopic‐assisted gastropexy (LAG) will not alter gastrointestinal transit times when comparing gastric (GET), small and large bowel (SLBTT), and whole gut transit times (TTT) before and after surgery.Animals10 healthy client‐owned large‐breed dogs.MethodsProspective clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…Since the population of dogs used in our study was composed of client-owned dogs of varying age, breed and size, it is difficult to compare these results with those obtained with purpose-bred research dogs. Indeed, our transit times more closely resemble those from a study investigating the effect of laparoscopic gastropexy on transit times in client-owned dogs (Balsa et al 2017). In that study, average capsule GET and TTT before surgery was in excess of 7 and 32 hours, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Since the population of dogs used in our study was composed of client-owned dogs of varying age, breed and size, it is difficult to compare these results with those obtained with purpose-bred research dogs. Indeed, our transit times more closely resemble those from a study investigating the effect of laparoscopic gastropexy on transit times in client-owned dogs (Balsa et al 2017). In that study, average capsule GET and TTT before surgery was in excess of 7 and 32 hours, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…In the long‐term follow‐up, the two dogs did not show any clinical signs related to gastrointestinal disease. Although no coefficient of variability was measured in the similar study, Balsa et al also had a large, albeit not statistically significant, variation in the GET range of over 1000 min when comparing GET before and after their laparoscopic‐assisted gastropexy …”
Section: Discussionmentioning
confidence: 83%
“…Although no coefficient of variability was measured in the similar study, Balsa et al also had a large, albeit not statistically significant, variation in the GET range of over 1000 min when comparing GET before and after their laparoscopic-assisted gastropexy. 33 One explanation for both of our GET variations could be that the WMC is not the best method for measuring physiological activity in the stomachs of dogs in a minimally invasive manner. Although it is beneficial that patients do not have to be exposed to radiation for their gastrointestinal transit time measurements, Lidbury et al found that gastric retention, even in healthy dogs weighing > 30 kg, was a risk.…”
Section: Discussionmentioning
confidence: 98%
“…Various methods such as conventional and contrast radiography, ultrasonography, nuclear markers, electromyography, radioactive tracers and motility capsules have been used to evaluate small intestinal motility (Caride et al 1984, Dromehl et al 1985, De Ridder et al 1989, Penninck et al 1989, Wiederkehr et al 1992, Choi et al 2001, Balsa et al 2017, in addition to radiopaque markers (Chandler et al 1990, Allan et al 1996, Chandler et al 1997, Sparkes et al 1997, Robertson & Burbidge 2000, Nelson et al 2001, Boscan et al 2006, Johnson et al 2017. Optimal dosing techniques of radiopaque markers in dogs include the use of 1.5-mm spheres fed in canned dog food, baby food or fed in a kibble ration.…”
Section: Discussionmentioning
confidence: 99%